Molecular genetic characterisation of Salem Black goats - Thilagam, K; Ramamoorthi, J; Sivaselvam, S N; Karthickeyan, S M K; Thanguraju, P (The Indian Journal of Animal Sciences, 2012)
The present investigation was carried out to study the genetic architecture of Salem Black goats, a distinct genetic group of goats in Tamil Nadu, which needs to be recognized as a breed. The genomic DNA samples from 50 unrelated Salem Black goats were evaluated with a panel of 21 microsatellite markers for genetic characterization. In these animals, the number of alleles ranged from 4 to 9 with a mean of 6.5 / locus. The sizes of alleles and their frequencies ranged from 74 to 206bp and from 0.0106 to 0.4642 respectively. Polymorphism information content ranged from 0.5710 to 0.8424 with a mean PIC of 0.7177. Except for four loci, the population was not in Hardy-Weinberg equilibrium. The observed heterozygosity ranged from 0.7804 to 1.0000 while the expected heterozygosity ranged from 0.6470 to 0.8541. The study revealed that there is high amount of genetic variation present in the population with the defined levels of heterosygosity and polymorphism information content. Hence, this distinct population of Salem Black goats could be recognized as a breed of goats in Tamil Nadu.